2015
DOI: 10.1371/journal.pone.0123691
|View full text |Cite
|
Sign up to set email alerts
|

Do Housekeeping Genes Exist?

Abstract: The searching of human housekeeping (HK) genes has been a long quest since the emergence of transcriptomics, and is instrumental for us to understand the structure of genome and the fundamentals of biological processes. The resolved genes are frequently used in evolution studies and as normalization standards in quantitative gene-expression analysis. Within the past 20 years, more than a dozen HK-gene studies have been conducted, yet none of them sampled human tissues completely. We believe an integration of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 93 publications
3
59
0
Order By: Relevance
“…The ICGs selected can significantly influence the results obtained. However, increasing evidence has shown that all of existing ICGs may vary depending the state of the cell or tissue, age and other experimental conditions (Zhang et al, 2015). Up to now, although numerous qPCR analyses have been conducted to improve IMF content, a through test for the expression stability of Figure 3 Determination of the optimal number of internal control genes for normalization as assessed by geNorm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ICGs selected can significantly influence the results obtained. However, increasing evidence has shown that all of existing ICGs may vary depending the state of the cell or tissue, age and other experimental conditions (Zhang et al, 2015). Up to now, although numerous qPCR analyses have been conducted to improve IMF content, a through test for the expression stability of Figure 3 Determination of the optimal number of internal control genes for normalization as assessed by geNorm.…”
Section: Discussionmentioning
confidence: 99%
“…GeNorm and NormFinder are two of the most commonly used method to screen stable ICGs required for qPCR normalization (Zhang et al, 2015). GeNorm identifies the most suitable genes by calculating the gene stability measure (M) values, which indicate the changes in gene expression with respect to other genes.…”
Section: Discussionmentioning
confidence: 99%
“…We compiled 12,501 HK genes from 15 studies using either MA or sequencing based transcriptomic techniques [12] in which we removed 13 genes annotated to Homo…”
Section: Data Collectionmentioning
confidence: 99%
“…ACCEPTED MANUSCRIPT 16 was much more sensitive and identified genes with much less expression levels [12].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation